The mitochondrial genome of Monoserius pennarius (Linnaeus, 1758) from the East China Sea - Jing Mo; Min Lu; Anning Mou; Xuetao Wang; Wenge Shi; Xuelei Zhang; Qinzeng Xu (Mitochondrial DNA. Part B. Resources, 2024)
AbstractThe species Monoserius pennarius (Linnaeus, 1758), is particularly abundant in the tropical Indo-West Pacific east of Sri Lanka, yet very limited genetic information exists for this species. Here, we report the assembled-linear mitochondrial genome of M. pennarius collected from the East China Sea. The 15,197 bp mitogenome contains 13 protein-coding genes (PCGs), two tRNA genes, and two rRNA genes. Notably, the gene order in this mitogenome differs from that of other hydrozoans within the same taxonomic order. Phylogenetic analysis, based on 13 concatenated mitochondrial PCGs, recovered M. pennarius as a sister of Nemalecium lighti (Hargitt, 1924), outside the other Leptothecata hydrozoans, suggesting paraphyly of Leptothecata. The mitogenome of M. pennarius, serving as the first publicly available for the family Aglaopheniidae, holds foreseeable value for investigating Leptothecata evolution.